EDUCATION AND THE INFLUENCE OF IDEOLOGY IN SOCIETY (EXAMINING MAX HORKHEIMER'S THEORY OF EDUCATION IN THE CONTEMPORARY SOCIAL CONTEXT) - Loppies, Imelda Jaqualine; Arlin, Arlin; Syamsul, Syamsul (Gema Kampus IISIP YAPIS Biak, 2025)
Education and the influence of ideology in society, according to Max Horkheimer, suggest that education is always linked to broader social structures, where schools and other educational institutions tend to reinforce the dominant ideology—often associated with capitalism and power relations in society. It also explains how dominant ideologies (such as capitalism, patriarchy, or racialism) are institutionalized within social institutions, including education. In the context of education, this means that curricula, teaching methods, and the structure of educational institutions tend to uphold values and ideologies that support the interests of the ruling class, rather than offering more critical or alternative perspectives. The objective of this research is to examine education and the influence of ideology through Max Horkheimer's theory. This study employs a qualitative literature review approach. The author emphasizes an analysis based on qualitative literature research, focusing particularly on Max Horkheimer's theories. The research findings include: The Application of Max Horkheimer's Theory in Understanding the Influence of Ideology in Education, Education from Horkheimer's Perspective, The Influence of Ideology in Contemporary Education, and Horkheimer's Theory in the Context of Contemporary Society.